Salmonella and Escherichia coli in Locally Fermented Milk Sold in Owerri, Nigeria: A Public Health Risk - A.I. Zanwa (RESEARCH JOURNAL OF FOOD SCIENCE AND QUALITY CONTROL, 2026)
A cross-sectional study was conducted in Owerri West to determine the prevalence of Salmonella and Escherichia spp. from 33 fermented milk samples (nono) that were randomly collected from milkmaids from various locations in Owerri West, Imo state, Nigeria. Standard microbiological methods were used to isolate the coliforms, a method described by Quinn et al. (2002). This study showed that 16 samples were positive for Salmonella and Escherichia coli, with E. coli having the highest prevalence at 11/33 (33.0%), followed by Salmonella at 5/33 (15.0%). Ama-Hausa Douglas revealed the highest prevalence for E. coli 5/18 (27.0%) and Salmonella spp. 3/18 (16.0%); followed by Mami market Obinze with E. coli 2/8 (25.0%) and Salmonella spp.1/8 (12.5%). Additionally, in Slaughter Garke, E. coli had 2/3 (66.0%) and Salmonella spp.1/3 (33.0%) accordingly. Furthermore, this study showed that Ama-Hausa Douglas had the highest microbial count for E. coli (8.0 × 104 CFU/mL). Milk sold for public consumption should be monitored strictly by public health enforcement officers; however, samples should be screened routinely to assess their microbial load, desirability, and ability to cause human food poisoning